Pengaruh Pengetahuan Investasi, Perilaku Keuangan Dan Pendapatan Terhadap Keputusan Investasi Mahasiswa Di Fakultas Ekonomi Universitas Se-Kota Denpasar - Damayanti, Pande Kadek Dian; Padnyawati, Kadek Dewi; Yuliantari, Ni Putu Yeni (UNHI Press, 2025)
An investment decision is a decision to allocate or place a certain amount of funds into a certain type of investment. It can also be said to be a step chosen by investors in their capital investment activities based on their considerations and experience. One of the factors needed in making investment decisions is investment knowledge, financial behavior and income. The aim of this research is to determine the influence of Knowledge, Financial Behavior and Income on Student Investment Decisions at the Faculty of Economics at Universities in Denpasar City. Research is quantitative or relates to numbers as a benchmark. Data was collected using a gform questionnaire using Stratified Random Sampling techniques. The number of samples in this research was 100 student respondents at the Faculty of Economics, Universities in Denpasar City using the Slovin Formula. Analysis techniques in research use descriptive analysis techniques, validity & reliability tests, classical assumption tests and multiple linear regression tests. The research results show that Investment Knowledge (X1) has a positive and significant effect on Investment Decisions (Y). Financial Behavior (X2) has a positive and significant effect on Investment Decisions (Y). Income (X3) has a positive and significant effect on Investment Decisions (Y).